Measurement of Differential Na+ Eﬄux from Apical and Bulk Root Zones of Intact Barley and Arabidopsis Plants - Hamam, Ahmed M.; Britto, Dev T.; Flam-Shepherd, Rubens; Kronzucker, Herbert J. (Frontiers in Plant Science, 2016)
Rapid sodium cycling across the plasma membrane of root cells is widely thought to be associated with Na+ toxicity in plants. However, the efflux component of this cycling is not well understood. Efflux of Na+ from root cells is believed to be mediated by SOS1, although expression of this Na+/H+ antiporter has been localized to the vascular tissue and root meristem. Here, we used a chambered cuvette system in which the distal root of intact salinized barley and Arabidopsis thaliana plants (wild-type and sos1) were isolated from the bulk of the root by a silicone-acrylic barrier, so that we could compare patterns of 24Na+ efflux in these two regions of root. In barley, steady-state release of 24Na+ was about four times higher from the distal root than from the bulk roots. In the distal root, 24Na+ release was pronouncedly decreased by elevated pH (9.2), while the bulk-root release was not significantly affected. In A. thaliana, tracer efflux was about three times higher from the wild-type distal root than from the wild-type bulk root and also three to four times higher than both distal- and bulk-root fluxes of Atsos1 mutants. Elevated pH also greatly reduced the efflux from wild-type roots. These findings support a significant role of SOS1-mediated Na+ efflux in the distal root, but not in the bulk root.